2020
DOI: 10.1136/heartjnl-2019-316118
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnoea and cardiovascular outcomes after coronary artery bypass grafting

Abstract: ObjectivePatients with advanced coronary artery disease are referred for coronary artery bypass grafting (CABG) and it remains unknown if sleep apnoea is a risk marker. We evaluated the association between sleep apnoea and major adverse cardiac and cerebrovascular events (MACCE) in patients undergoing non-emergent CABG.MethodsThis was a prospective cohort study conducted between November 2013 and December 2018. Patients from four public hospitals referred to a tertiary cardiac centre for non-emergent CABG were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Numerous studies have demonstrated the associations of sleep apnea with various short-and long-term complications after CABG, including new-onset atrial brillation, respiratory complications, hospital readmission, and major adverse cardiac and cerebrovascular events (MACCEs) [12][13][14][15]. These ndings were corroborated by the recently published results of the SABOT (Sleep Apnea and Bypass Operation) study, which revealed an association of sleep apnea with a 1.57-fold increase in the risk of developing MACCEs [16].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Numerous studies have demonstrated the associations of sleep apnea with various short-and long-term complications after CABG, including new-onset atrial brillation, respiratory complications, hospital readmission, and major adverse cardiac and cerebrovascular events (MACCEs) [12][13][14][15]. These ndings were corroborated by the recently published results of the SABOT (Sleep Apnea and Bypass Operation) study, which revealed an association of sleep apnea with a 1.57-fold increase in the risk of developing MACCEs [16].…”
Section: Introductionmentioning
confidence: 73%
“…No previous study on the association between DM and CABG outcomes has reported the additional prognostic effect of sleep apnea [3][4][5][6][7][8]. Recently, two relatively large-scale studies demonstrated an independent association of sleep apnea with adverse cardiovascular events in patients undergoing CABG and major non-cardiac surgery [16,25]. The predictive effects of sleep apnea and DM for adverse cardiovascular events were reported to be additive in patients undergoing percutaneous coronary intervention [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it seems legitimate to conduct diagnostics in this group of patients, given the fact that the prognosis is worse if OSA is left untreated [24]. A recent study involving more than 1,000 patients with advanced coronary artery disease eligible for coronary artery bypass grafting (CABG) [25] also showed that moderate and severe OSA was common, occurring in 50.9% of individuals in this group of patients. The study also proved that in patients with coronary artery disease, OSA was an independent factor contributing to major cardiovascular events, including death.…”
Section: Osa and Cardiovascular Diseasesmentioning
confidence: 99%
“…Sixteen studies reported an increased Hazard ratio (HR) of MACCEs outcomes with SDB compared with controls in patients with myocardial ischemia, 12,13,16,18,19,20,21,22,23,24,25,26,27,28,29,30 with the combined HR of 1.66(95% CI 1.41-1.94, P< 0.0001) (Fig 2). Some evidence of statistical heterogeneity (Cochran Q = 23.00, p=0.08; I 2 = 35%) was found by pooled effect size, which might be in part attributable to 1 randomized controlled trial.…”
Section: Major Adverse Cardiovascular or Cerebrovascular Events (Macces)mentioning
confidence: 99%